BERNSTEIN AND FOUCAULT ON EPISTEMIC DIVERSITY AND CURRICULUM TRANSFORMATION - Victor J. Pitsoe; Thulani Zengele (Social Sciences and Education Research Review)
Both decolonization and curriculum democratisation have emerged as major talking points in discourses about higher education. The premise of this article is that curriculum change in higher education should be fueled by social context responsiveness, epistemic diversity, pedagogical innovation, classroom practises renewal, and an institutional culture of candour and critical reflection. The Fourth Industrial Revolution and post-COVID-19 pose problems for the existence of epistemic diversity and diversity management in the discourse of curriculum transformation in higher education, according to this conceptual article (4IR). Epistemic diversity and diversity management are concepts that, in our opinion, have the characteristics of an Althusserian Ideological State Apparatus that can advance the political objectives of the post-COVID-19 and 4IR spaces.